The Effectiveness of Direct Method in Arabic Language Learning - Zahro, Umi Chabibatus; Amalia, Sofri Rizka; Amin, Nur Fadilah (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2020)
Understanding of arithmetic students in Arabic learning is still low. This study aims to determine the effectiveness of the Direct Method in learning Arabic number material in Arabic understanding Arithmetic Students. The approach used is experimental research approach with Posttest-Only Control Design. The population and sample of the study were determined through the Random Sampling technique. Analysis of the data used included normality test, homogeneity test, average similarity test, completeness test, and comparative test. (1) the arithmetic understanding of students taught by the Direct Method in learning ‘Adad dan Ma’dud material can exceed the Standard of Minimum Mastery (KKM) of 76,87, (2) the arithmetic understanding of students taught by the Direct Method is 76,87 higher than from the conventional models 65,32. Then it can be concluded that the Direct Method is effective in understanding arithmetic in learning ‘Adad dan Ma’dud material. The novelty of this research is that using the Direct Method can facilitate a direct understanding of 'adad and ma'dud.This research contributes in Arabic teaching by using the Direct Method in the material 'Adad and Ma'dud to improve students' arithmetic understanding.